(untitled) (Research in Agriculture Livestock and Fisheries, 2024)
The association between body and udder measurements can be used towards the improvement of milk yield. Hence, this study aimed to identify the udder measurement traits and body measurement traits that may be used by farmers to increase milk yield of Holstein cows. The study was conducted at Limpopo Dairy Farm in Makhado Local Municipality at Louis Trichardt, Limpopo Province, South Africa where a total of 50 lactating Holstein cows were used. Pearson’s correlation technique was used for data analysis. Findings between body measurement traits and milk yield showed that milk yield had a highly positive significant (p ˂ 0.01) correlation with rump height (r = 0.55), and positive significant (p < 0.05) with withers height (r = 0.44) and body length (r = 0.42). Results between udder measurement traits and milk yield showed that milk yield had a highly positive significant (p < 0.01) correlation with udder length before milking (r = 0.57), udder circumference before milking (r = 0.55) and udder circumference after milking (r = 0.51) The results also showed that milk yield had a positive significant (p < 0.05) correlation with teat diameter before milking (r = 0.30), teat length before milking (r = 0.31), teat circumference before milking (r = 0.36) and udder length after milking (0.47). The findings imply that all traits correlated with milk yield can be used to enhance milk yield of Holstein cows through selection during breeding. Vol. 10, No. 3, December 2023: 335-340